a Analysis Of Student Responses Toward Sets-Based Discovery Learning - Aisha Azalia; Arief Muttaqiin (Universe, 2020)
This study aimed to describes student responses to the SETS-based discovery learning in class VII.1 of SMP N 30 Padang. The form of study was research sample were by questionnairre to 30 students. Data were collected using questionnaire for classroom learning process including response and also reaction criteria with interest in learning and critical thinking students. The data were analysed by using likert scale, and the research results showed that the learning process was conducted with data analysis is good. This study prove that SETS based discovery leaning was very suitable for teaching of interaction of living things and giving positive respon from students.